Knowledge Management: Efforts to Create an Excellent Digital Creative Industry - Lukmanul Hakim Aufa Pringgo Prawira; Aulia Fahirah Ummah; Muhamad Reza Aditiya; Dimas Widi Nugroho (Startupreneur Business Digital (SABDA Journal), 2023)
As a sub-sector of the creative industry, which is a priority in the third stage of national creative industry development, the digital creative industry should be further developed through appropriate strategies. The heart of the industry is ideal for creating creative digital products. If not managed, it is difficult to transform each individual's ideas into organizational knowledge. Knowledge management as a medium for managing ideas can transform individual knowledge into shared knowledge. This research is qualitative. The sampling technique used is targeted sampling. Respondents of this survey are digital creative businessmen from Bandung City who have a deep understanding of the knowledge management process. Data were collected by observational methods, questionnaire distribution, and in-depth interviews. The survey found that the digital creative industry in Bandung City is facing problems in implementing effective knowledge management. Personal knowledge, work processes, and possession of technology were not optimally implemented to complete the work.